(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
male with an unusual firearm entry wound on the surface of the small intestinal loop, which was surgically exposed (open laparotomy wound), causing extensive internal damage and hemorrhage. The bullet recovered from the subcutaneous plane on the right side of the abdomen. The death was due to hemorrhagic shock caused by a firearm injury to the internal abdominal organs. What sets this case apart in the literature is not just the tragic nature of the event but the context in which it occurred—a hospital, a place inherently associated with safety and healing. In the landscape of forensic and medical literature, this case stands out because of the intersection of violence and healthcare, which challenges the norms of both fields. This incident highlights the critical need for enhanced security measures in hospitals to prevent violence against patients and doctors. This examination not only provides crucial insights into the nature of gunshot wounds and their impact on internal organs but also emphasizes the broader implications for hospital security and patient safety.